A Randomized Controlled Trial on the Effectiveness of Intrathecal Tramadol Versus Buprenorphine as Adjuvants to Hyperbaric Bupivacaine in Infraumbilical Surgeries - Muhammad Javed Khan, Attique Ur Rehman Orakzai, Faiza Aslam, Hamid Mehmood, Pavan Kumar, Nazneen Iqbal, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Effective postoperative analgesia is crucial in infraumbilical surgeries. This study aims to compare the efficacy of intrathecal tramadol and buprenorphine as adjuvants to hyperbaric bupivacaine. Methods: A total of 155 patients undergoing elective infraumbilical surgeries were assigned to three groups: Group I (n=52) received 10 mg of 0.5% hyperbaric bupivacaine with 30 mg tramadol; Group II (n=51) received 10 mg of 0.5% hyperbaric bupivacaine with 50 µg buprenorphine; Group III (n=52) received 10 mg of 0.5% hyperbaric bupivacaine with saline. The primary outcomes were the duration of postoperative analgesia and total analgesic consumption. Secondary outcomes included the onset time of sensory and motor blocks, hemodynamic stability, and incidence of side effects. Results: Group I showed a significantly longer duration of postoperative analgesia compared to Group II and Group III. The total analgesic consumption was lowest in Group I. The onset time for sensory and motor blocks was similar across all groups. Hemodynamic parameters remained stable, with minimal and comparable side effects across the groups. Conclusion: Intrathecal tramadol provides superior postoperative analgesia with reduced analgesic consumption compared to buprenorphine and saline when combined with hyperbaric bupivacaine. Keywords: Intrathecal tramadol, buprenorphine, hyperbaric bupivacaine, postoperative analgesia, infraumbilical surgeries, randomized controlled trial.